Effects of Chlorine Application on Bactericidal Efficiency at Municipal Wastewater Treatment Plant - Lee, Un-gi; Lee, Yoon-jin; Nam, Sangho (Asian Journal of Chemistry, 2010)
This research was performed to evaluate the inactivation rate of indicator microorganisms such as total coliform, fecal coliform, fecal streptococcus and the effect of water parameters when chlorine is applied as a disinfectant in the discharged water at the J municipal wastewater treatment. Based on these results, it presented the empirical equation for estimating the number of these indicator microorganisms. The value of LC50 (median lethal concentration) for 24 h was 0.8 mg/L by the acute toxicity test of Oryzias latipse. The formation of disinfection by-product such as trihalomethanes (THMs) and haloacetic acids (HAAs) which are known as carcinogens was evaluated on chlorine dose in discharged sewage water to examine the sanitary and ecological facts during chlorination.